Optimizing School-Based Management Effectiveness through the Integration of POACE and SWOT Analysis - Della Nurul Arsita; Muhammad Aditia Prasetyo; Siti Amelia Wati; Zaera Khuswatun Khasanah; Yenny Merinatul Hasanah (Journal of Educational Management Research, 2026)
This study aims to analyze the implementation of POACE (Planning, Organizing, Actuating, Controlling, and Evaluating) and SWOT analysis in improving the effectiveness of School-Based Management (SBM) at an Islamic vocational school. A descriptive qualitative approach was employed using observations, semi-structured interviews, documentation, and data triangulation to ensure the credibility of the findings. Data were analyzed through the interactive model of data condensation, data display, conclusion drawing, and verification. The findings reveal that the school has successfully established a strong Islamic culture, effective organizational governance, structured disciplinary practices, and integrated extracurricular and vocational programs that support institutional effectiveness. However, challenges remain in implementing data-driven planning, strengthening industry partnerships, enhancing teacher professional competence, expanding Teaching Factory programs, and developing performance-based evaluation systems. The study concludes that integrating POACE with SWOT provides a comprehensive strategic management framework that strengthens School-Based Management through systematic planning and continuous improvement. The findings offer both theoretical contributions to educational management literature and practical guidance for vocational schools seeking sustainable institutional quality improvement through evidence-based management.